AB0198 SMOKING AND POSITIVITY OF RHEUMATOID FACTOR AND ANTI-CYCLIC CITRULLINATED PEPTIDE ANTIBODY IN THE GENERAL POPULATION. (2nd June 2020) - Kidoguchi, G.; Fukui, S.; Nakai, T.; Kawaai, S.; Ozawa, H.; Ikeda, Y.; Koido, A.; Ohara, Y.; Shimizu, H.; Yamaguchi, K.; Tamaki, H.; Okada, M.
Abstract : Background: It is well known that rheumatoid arthritis (RA) occurs due to environmental risk factors in addition to genetic risk factors. Rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibody (ACPA) are strongly associated with RA, and these biomarkers could turn to be positive before development of clinical symptoms. While smoking, particularly Brinkman index (BI) is well known as a risk factor for RA and ACPA positivity, it is still unclear whether smoking intensity or smoking duration contribute more to positive RF and ACPA. Objectives: This study aims to evaluate risk factors for RF and ACPA positivity in the general population. It also describes whether smoking intensity, duration, and BI are significant. Methods: This is a cross-sectional, observational, single center study. We reviewed the baseline characteristics of the general population who checked RF and ACPA at Preventive Medicine Center in St. Luke's International Hospital, Tokyo, Japan from January 2004 to December 2018. The data for basic demographics, dietary habit, smoking intensity, smoking duration, BI, and blood tests including RF and ACPA were extracted. The data was analyzed statistically. Results: A total of 127472 people who checked RF are included. Of these 127472 people, 64504 (50.6%) are male and the mean age was 44.9 years. RF was positive in 11477 people (9.0%). Among these, 1667 (1.2%) were checked for ACPA, and 21 people (1.3%) had positive ACPA. None of variables demonstrated significant association with RF positivity. In contrast, BI and smoking duration was significantly associated with an increased risk of ACPA positivity (13.3 years vs 7.49 years, p value = 0.023), although the number of cigarettes smoked was not. The smoking duration for 10 years or more was associated with an increased risk of ACPA positivity even after adjusted for age and sex (adjusted hazard ratio: 2.47 [95% confidence interval: 1.04-5.87]; p=0.04). Conclusion: In this study, no significant risk factor for positive RF was found. Even smoking was not associated with RF positivity. On the other hand, smoking duration, not smoking intensity was significantly associated with an increased risk of ACPA positivity. References: [1]Verpoort KN. Association of smoking with the constitution of the anti-cyclic citrullinated peptide response in the absence of HLA-DRB1 shared epitope alleles. Arthritis Rheum 2007;56:29138. Disclosure of Interests: None declared